Immunoprobe development for detection of Ralstonia solanacearum in potato (Solanum tuberosum) and tomato (Solanum lycopersicum) - KHAN, MD RASHID; AKHTAR, JAMEEL; PUNDHIR, V S; KUMAR, ANIL (The Indian Journal of Agricultural Sciences, 2026)
Anti-potato and anti-tomato polyclonal antibodies were developed for serodiagnosis of bacterial wilt. Optimum antigen concentration was standardized as 7.5 ×106 cells for potato (Solanum tuberosum L.) and 5 × 107 cells for tomato(Solanum lycopersicum L.) per well and dilution of antibacterial antibody was optimized as 1:250 for potato and 1:175 for tomato strains for indirect enzyme-linked immunosorbent assay (ELISA). As small as 1 × 104 bacterial cells were detected by indirect ELISA which showed the greater affinity of raised polyclonal anti-bacterial antibodies for its antigen and higher sensitivity for detection of bacterial pathogen in suspected plants. In the reactivity test of the bacterial isolates with antibodies, all the isolates of R. solanacearum identified through conventional methods, showed positive results. All the tomato isolates reacted with both the antibodies. The pathogenic isolates of chilli could not be identified by both the antibodies. The cross reactivity of anti-potato antibodies with only chilli strain of R. solanacearum suggests the specificity of these polyclonal antibodies against these strains. While, other strains, except chilli strain, indicates non-homology of antigenic epitopes of bacterial wall proteins with virulent potato strain.